Paradoxes of Experience: Questioning the Limits of Phenomenality in E. Levinas and J.-L. Marion - Norus, Laurynas (Problemos, 2022)
The article deals with the problem of the limits of phenomenality in the phenomenology of E. Levinas and J.-L. Marion. D. Janicaud attributes their positions to a “theological turn” in French phenomenology. Without polemicizing directly with Janicaud, the article does not treat that turn as a distortion or neglect of the phenomenological method and its principles. On the contrary, the author sees it as focusing on those aspects of experience that do not fit into the scope of Husserlian phenomenology, decentering the experiencing subject and forcing us to rethink the very question of phenomenality and its limits. The article aims to show that, despite quite radical and controversial transformations in phenomenology, Levinas and Marion base their phenomenological projects by analysing not a special or “mystical” but accessible to all, in a sense, a banal experience.
Keywords: alterity; Other; phenomenology; theological turn; Levinas; Marion